Forensic Analysis of Fire Debris and Explosives - Evans-Nguyen, Kenyon; Hutches, Katherine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This text provides training on the fundamental tools and methodologies used in active forensic laboratories for the complicated analysis of fire debris and explosives evidence. It is intended to serve as a gateway for students and transitioning forensic science or chemistry professionals. The book is divided between the two disciplines of fire debris and explosives, with a final pair of chapters devoted to the interplay between the two disciplines and with other disciplines, such as DNA and fingerprint analysis. It brings together a multi-national group of technical experts, ranging from academic researchers to active practitioners, including members of some of the premier forensic agencies of the world. Readers will gain knowledge of practical methods of analysis and will develop a strong foundation for laboratory work in forensic chemistry. End-of-chapter questions based on relevant topics and real-world data provide a realistic arena for learners to test newly-acquired techniques.
1. Introduction to instrumentation used in FD/E analysis (Kenyon Evans-Nguyen, Associate Professor, University of Tampa) -- 2. Fire debris analysis: general introduction to how it is currently done (Mark Sandercock, Team Lead - Trace Evidence, Royal Canadian Mounted Police) -- 3. Microbial degradation of ignitable liquids (Katherine Hutches, Forensic Chemist, Bureau of Alcohol, Tobacco, Firearms and Explosives) -- 4. Background interferences in fire debris analysis (Jamie Baerncopf and Sherrie Thomas, Forensic Chemists, Bureau of Alcohol, Tobacco, Firearms and Explosives) -- 5. Alternative Fuels: E85, biodiesel, vegetable oils, etc. (Doug Byron, Forensic & Scientific Testing, Inc and Raymond Kuk, Section Chief, Bureau of Alcohol, Tobacco, Firearms and Explosives) -- 6. Variation in gasoline/general IL variation within classes (Susan Hetzel, Senior Analytical Chemist, SEA Limited and Mary Williams, Coordinator of Research Programs & Services, National Center forForensic Science, University of Central Florida) -- 7. Explosives analysis: general introduction to intact analysis of explosives (Hazel Hutson, Principal Case Officer, Defence Science and Technology Laboratory and Eamonn McGee, Senior Forensic Technologist, Centre of Forensic Sciences) -- 8. Explosives analysis: introduction to post-blast analysis (Brittany Crane-Calhoun, Forensic Chemist, Bureau of Alcohol, Tobacco, Firearms and Explosives and Robert Mothershead II, Supervisory Chemist - Forensic Examiner, Federal Bureau of Investigation) -- 9. Componentry (Kirk Yeager and Kathy Boyle, Forensic Chemists, Bureau of Alcohol, Tobacco, Firearms and Explosives) -- 10. Battlefield Forensics (James Garcia, Head of Trace Analysis and Chemistry, Defense Forensic Science Center and Robert Ollis, Forensic Chemist, Defense Forensic Science Center) -- 11. Fire debris/explosives overlap: flares/fusees, thermite, ANFO (Michelle Evans, Forensic Chemist, Bureau of Alcohol, Tobacco, Firearms and Explosives) -- Index.
Keywords: Analytical chemistry; Fire prevention; Buildings -- Protection; Forensic sciences; Materials -- Analysis; Security systems; Building materials; Analytical Chemistry; Fire Science, Hazard Control, Building Safety; Forensic Science; Characterization and Analytical Technique; Security Science and Technology; Building Materials